Optimization Quality of Multi-resolution Image De-Noising Schemes using Wavelet Transforms (International Journal of Communication Systems and Network Technologies, 2022)
Image de-noising is a central issue in picture handling.The primary goal is to eliminate noise from the deteriorated image while maintaining other image details. Lately, numerous multiresolution based approaches have achieved extraordinary progress in image denoising. In a nutshell, the wavelet transform provides the optimal representation of a noisy image, with noise caused by all remaining coefficients and information bearing signal from a small number of coefficients. The loud coefficients can be killed by thresholding system. Thus, there are three fundamental steps in every waveletbased image denoising technique: to determine the inverse wavelet transform, threshold the wavelet coefficients, and compute the noisy image’s wavelet transforms. The image’s capacity for sparse representation determines how well the noisy coefficient separation works. The wavelet portrayal is ideally scanty, since the wavelets covering a peculiarity have a huge wavelet coefficient and any remaining coefficients are little. Only when the threshold value is chosen appropriately can the noise wavelet coefficient shrinkage be improved to its absolute best.
Keywords: Optimization; De-noising; Wavelet Transform; Thresholding System; Noisy Image; Wavelet-based Image De-noising Technique